The Influence of Community Perception on Family Planning Participation: A Case Study in Padang Sarai Village Koto Tangah District Padang City - Meidara, Lovita; Malau, Hasbullah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the influence of community perceptions on family planning participation in Padang Sarai Village. Quantitative methods were used in this study and used a sample of 100 people who met the criteria for married status and domiciled in Padang Sarai Village. Data collection was carried out through distributing questionnaires which became the primary data source. The collected data was analyzed using instrument tests via the SPSS Version 25 for Windows program to assess the validity and reliability of the data. The results of the analysis show that the perception variable has a consequent on participation. This is supported by hypothesis testing which produces a perceived significance value (Sig) of 0.000 < 0.05 and tcount 14.476 > ttable 1.984.